Financial Performance's Impact on Tax Avoidance - Rinaldi, Muhammad; Aulia Ramadhani , Melda; Sudirman , Sitti Rahma; Khatib Ramadhani , Muhammad Harits Zidni (Eastasouth Institute, 2023)
The issue in this study is Indonesia's inability to realize its full potential in terms of tax income, which is declining every year. This study investigates how tax avoidance is impacted by profitability and Leverage. For the Indonesia Stock Exchange (IDX) population in 2017–2019, 73 manufacturing firms in the Basic and Chemical Industry category were selected. So that 28 businesses satisfied the requirements, the sample was chosen using purposive sampling. The study concludes that profitability discourages tax evasion. Therefore, the corporation is more likely to engage in tax evasion the lower its profitability value. Leverage has no bearing on tax evasion. Hence businesses with high or low debt ratios can engage in it. Another result that can be justified is that.